The Effect of Marketing Mix 7P on Visit Intention Eco-Tourism at Seloliman Mojokerto - Septyanto Putri, Ervina; Perwangsa Nuralam, Inggang (Profit: Jurnal Adminsitrasi Bisnis, 2024)
Seloliman Environmental Education Center is an alternative educational tour for students, residents, and tourists. Based on phenomena that occur in the field, visitors are only crowded during certain seasons and moments. At other times, visiting tourists did not experience a significant increase. This research aims to analyze the Marketing Mix 7P variable against the Visit Intention variable at the Seloliman Environmental Education Center, Mojokerto Regency. This research is explanatory. The analytical method in this research is descriptive analysis and multiple linear regression analysis. This research data was obtained by distributing questionnaires directly and online to 155 respondents. The sampling technique in this research was the purposive sampling method. The data used in this study are primary data and secondary data. The data analysis techniques used are descriptive and moderated regression. The data in this study was processed using SPSS ver 22. The results of this research show that the variables Product, Price, Place, Promotion, People. Process and Physical Evidence have a positive and significant influence on the Visit Intention (Y) variable at the Seloliman Environmental Education Center, Trawas.